Rural Elementary Teachers and Place-Based Connections to Text During Reading Instruction - Rachel Waller; Shelby J. Barrentine (Journal of Research in Rural Education, 2015)
Schooling can play a role in bolstering a sense of community, but research suggests that curriculum may serve to isolate teachers and students from their rural surroundings. In this qualitative case study, we asked if the literacy curriculum and instruction supported readers to make connections to their rural setting. We analyzed curriculum materials, fi eld notes from classroom observations, and interview transcripts of teachers to describe elementary students' opportunities to make connections to their rural setting. Analysis revealed that the commercial curriculum provided limited support for making connections to readers' rural backgrounds. Further, although teachers were interconnected with the rural community, attempts to weave complex connections to place were rare. Findings suggest that the curriculum fell short of integrating the community and the world. Rather, the rural teacher was the source for guiding students to make place-based connections.